2016
DOI: 10.1016/j.bbi.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Young women post-MI have higher plasma concentrations of interleukin-6 before and after stress testing

Abstract: Objectives Young women have poorer prognosis after myocardial infarction (MI) and a higher rate of mental stress-induced ischemia compared with similarly aged men. A higher inflammatory status may help explain these sex differences. Methods We examined 98 patients (49 women and 49 men) age 18–59 years with recent MI (past 6 months). Women and men were matched for age, type of MI, and time since MI. Interleukin 6 (IL-6) concentrations were measured at baseline, after mental stress using a speech task, and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…They also show an increase in negative emotions with non-psychological stressors, such as an inflammatory challenge with endotoxin, even though the inflammatory response is similar (Moieni et al, 2015). The similar physiological response to an inflammatory stimulus in women compared with men in this experimental study parallels the finding that young women with a previous history of MI show the same inflammatory response to mental stress as age-matched men; however, women exhibit double the level of interleukin-6 (IL-6) than men, both at baseline and at 90 min after the stress challenge (Rooks et al, 2016). Even in absence of CHD, women exhibit higher levels of C-reactive protein, a commonly studied inflammatory marker, compared with men of similar age, starting at age 16, potentially due to the onset of menarche (Ford et al, 2003; Wener et al, 2000; Woloshin and Schwartz, 2005).…”
Section: Emotional Factors and Coronary Heart Disease In Womensupporting
confidence: 79%
See 2 more Smart Citations
“…They also show an increase in negative emotions with non-psychological stressors, such as an inflammatory challenge with endotoxin, even though the inflammatory response is similar (Moieni et al, 2015). The similar physiological response to an inflammatory stimulus in women compared with men in this experimental study parallels the finding that young women with a previous history of MI show the same inflammatory response to mental stress as age-matched men; however, women exhibit double the level of interleukin-6 (IL-6) than men, both at baseline and at 90 min after the stress challenge (Rooks et al, 2016). Even in absence of CHD, women exhibit higher levels of C-reactive protein, a commonly studied inflammatory marker, compared with men of similar age, starting at age 16, potentially due to the onset of menarche (Ford et al, 2003; Wener et al, 2000; Woloshin and Schwartz, 2005).…”
Section: Emotional Factors and Coronary Heart Disease In Womensupporting
confidence: 79%
“…Since these disturbances have been linked to ambulatory ischemia and MSIMI (Burg et al, 2014; Gullette et al, 1997a; Wei et al, 2014a), it is possible that repeated, cumulative distress in everyday life leads to a chronic form of microvascular diastolic dysfunction which is present at baseline and predicts MSIMI (Ersboll et al, 2014). All these potential vascular effects may be accentuated in young women given their higher baseline levels of inflammation (Rooks et al, 2016). Thus, the fact that vascular dysfunction is an important mechanism of MSIMI could explain a female predominance of this phenomenon.…”
Section: Emotional Factors and Coronary Heart Disease In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported a greater increase in depressed mood and feelings of social disconnection in healthy young women compared to men after exposure to an inflammatory challenge with endotoxin, even though the inflammatory response was similar . Similarly, in a previous study, we found that women ≤50 years with a recent MI had a similar inflammatory response to stress than men, but the level of interleukin‐6 was 2 times higher in women than men before, during, and after the stress challenge . It is possible that the high absolute levels of inflammation reached during stressful events pose young women above a threshold of risk for abnormal emotional and vascular responses to stress.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, it is possible that women exhibit enhanced microvascular dysregulation with mental stress due to their propensity to vasomotor reactivity 74 . Stress-induced vasoconstriction could be accentuated in young women given their higher baseline levels of inflammation 75 . Overall, these studies have uncovered vulnerability for adverse effects of emotional stress on cardiovascular function in women.…”
Section: Cardiac Risk Factorsmentioning
confidence: 99%